The Way of Heaven Follows Its Own Course: A Review of Huang Yinnong’s “Mastering Heaven’s Mandate: Astrology, Divination, and Ancient Chinese Society” - SUN, Hanyu (Journal of Research for Christianity in China (JRCC), 2025)
Review of “Mastering Heaven’s Mandate: Astrology, Divination, and Ancient Chinese Society”